Relationship and effect of miR-1-3p expression and BDNF level in patients with primary hypertension complicated with depression - Ding, Jihong; Jiang, Chunyu; Yang, Le; Wang, Xianyan (Cellular and Molecular Biology, 2022)
This experiment was designed to explore the relationship and effect of miR-1-3p expression and BDNF level in patients with primary hypertension complicated with depression. The subjects of the study were 145 patients with hypertension with a small fluctuation range of blood pressure in recent three months. Within 48 hours after admission, patients were evaluated with the Hospital Anxiety and Depression Scale (HADS) and Hamilton Depression Rating Scale (HAMD). After fasting for 12 hours, enrolled subjects were subject to blood collection (5 ml) in the morning for detecting blood lipid levels, miR-1-3p expression and BDNF by using an automatic biochemical analyzer, real-time fluorescence quantitative PCR (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA), respectively. Results showed that compared with the normal control group, while miR-1-3p expression increased obviously in patients with hypertension, while the level of BDNF decreased significantly; and compared with patients with simple hypertension, the expression of miR-1-3p in hypertension patients with depression was significantly increased, while BDNF level was decreased evidently (All P < 0.05). miR-1-3p expression in patients with hypertension complicated with depression was negatively correlated with serum BDNF level (r=-0.302, P < 0.05). In relative to the normal control population, the area under the curve (AUC) of ROC produced by serum miR-1-3p and BDNF in patients with primary hypertension complicated with depression was 0.971 (95% CI = 0.945-0.998, P < 0.0001) and 0.875 (95% CI = 0.808-0.942, P < 0.0001); and in relative to primary hypertension patients without depression, the AUC of ROC produced by serum miR-1-3p and BDNF in patients with primary hypertension with depression was 0.957 (95% CI = 0.925-0.989, P < 0.0001) and 0.883 (95% CI = 0.821-0.944, P < 0.0001), respectively. HADS-D score, HAMD score, course of the disease, miR-1-3p expression and BDNF level showed statistical differences in primary hypertension patients with and without depression (All P < 0.05). It was concluded that there are high miR-1-3p expression and low serum BDNF levels in patients with primary hypertension complicated with depression. miR-1-3p has a negative correlation with BDNF, and it may play a role by negatively regulating the expression of BDNF. Detecting miR-1-3p and BDNF in patients with primary hypertension can indicate the occurrence of depression to some extent.